Accessing 1,2-Substituted Cyclobutanes through 1,2-Azaborine Photoisomerization - Giustra, Zachary X. (Angew Chem Int Ed Engl, 2019)
We provide a seminal example of the utility of the 1,2-azaborine motif as a 4C+1N+1B synthon in organic synthesis. Specifically, conditions for practically scalable 1,2-azaborine photoisomerization in a flow reactor are reported to furnish aminoborylated cyclobutane derivatives. C-B bond functionalizations to furnish a diverse set of highly substituted cyclobutanes were also achieved.